Lake Superior Paper - The Michigan College of Mines - M. E. Wadsworth (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1898)
The Michigan State College of Mines was established ten years ago last September as the fourth and last of the iustitutions of Michigan which are devoted to higher education. From the moment of its inception its single object has been to send out men who are qualified to take active part in the development of the mineral wealth of our State and nation, and any study which is essential to this end will not be found wanting in its courses of instruction. The institution has been singularly happy in its location. It is an axiom of modern education that any school which is to obtain the greatest return for the money and energy spent in